Peningkatan Keterampilan Membaca Pemahaman Teks Deskripsi Melalui Model Pembelajaran Berdiferensiasi Pada Siswa Kelas VII E SMP Negeri 2 Tegaldlimo Tahun Pelajaran 2024/2025 - Dinanti Shela Mahasiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to improve the reading comprehension skills of descriptive texts in class VII E students of SMP Negeri 2 Tegaldlimo through a differentiated learning model, with the method of differentiation of content, process, and product. This type of research is Classroom Action Research with the research subjects of class VII E students of SMP Negeri 2 Tegaldlimo in the 2024/2025 academic year with a total of 37 students. Data collection techniques include observation, interviews, questionnaires, tests, and documentation. Data analysis techniques use qualitative and quantitative descriptive analysis. The results of the study show that the application of a differentiated learning model can improve the reading comprehension skills of descriptive texts of class VII E students, especially in SMP Negeri 2 Tegaldlimo with two cycles, namely cycle I and cycle II. In cycle I, the completeness of reading comprehension skills of descriptive texts was 25 students with a percentage of 67.6%. In cycle II, the completeness of reading comprehension skills of descriptive texts was 37 students with a percentage of 100%. So the increase in reading comprehension skills of descriptive texts in cycle I to cycle II increased by 32.4%.
Reaploud Repository February_Hasyim
Keywords: Descriptive Text Comprehension Reading Skills and Differentiated Learning Model